Dealing with Climate Change Crisis - Oli, Krishna Prasad; Dhakal, Tara Devi; Pradhan, Navraj (The Initiation, 2010)
Climate change and its impact on human survival have been today's major challenge and key topics of discussion globally. When considering the catastrophic impacts climate change will bring to earth, in-depth studies on the mechanics and chemistry of climate changes has been emerging. Simultaneously, international and national policies to reduce the vulnerability from climate change have been developed. This article discusses environmental retrospect and climate change issues and highlights efforts taken by global community to reduce GHG. An analysis through an equity lens is made between developed and developing nations and distinction of science and post normal science, and how skeptics revolve around the myth of climate changing ‘naturally' is discussed. A brief status of climate change in Nepal has been mentioned and some mitigation and adaptation measures that can be carried out at the institutional and individual level to start solving the climate crisis conclude the paper. Key Words: Global warming, Climate change, International policies, Intra- generational equity, GHG, Renewable energy, Individual adaptation DOI: 10.3126/init.v2i1.2527 The Initiation Vol.2(1) 2008 pp79-90